Retinol Dehydrogenase-10 Regulates Pancreas Organogenesis and Endocrine Cell Differentiation via Paracrine Retinoic Acid Signaling. - Arregi, I; Climent, M; Iliev, D; Strasser, J; Gouignard, N; Johansson, J; Singh, T; Mazur, M; Semb, H; Artner, I; Minichiello, L; Pera, E (Oxford University Press, 2016)
Vitamin A-derived retinoic acid (RA) signals are critical for the development of several organs, including the pancreas. However, the tissue-specific control of RA synthesis in organ and cell lineage development has only poorly been addressed in vivo. Here, we show that retinol dehydrogenase-10 (Rdh10), a key enzyme in embryonic RA production, has important functions in pancreas organogenesis and endocrine cell differentiation. Rdh10 was expressed in the developing pancreas epithelium and surrounding mesenchyme. Rdh10 null mutant mouse embryos exhibited dorsal pancreas agenesis and a hypoplastic ventral pancreas with retarded tubulogenesis and branching. Conditional disruption of Rdh10 from the endoderm caused increased mortality, reduced body weight, and lowered blood glucose levels after birth. Endodermal Rdh10 deficiency led to a smaller dorsal pancreas with a reduced density of early glucagon(+) and insulin(+) cells. During the secondary transition, the reduction of Neurogenin3(+) endocrine progenitors in the mutant dorsal pancreas accounted for fewer α- and β-cells. Changes in the expression of α- and β-cell-specific transcription factors indicated that Rdh10 might also participate in the terminal differentiation of endocrine cells. Together, our results highlight the importance of both mesenchymal and epithelial Rdh10 for pancreogenesis and the first wave of endocrine cell differentiation. We further propose a model in which the Rdh10-expressing exocrine tissue acts as an essential source of RA signals in the second wave of endocrine cell differentiation.